Comprehensive review on mechanistic insights, optimal dosages, and safety prospective of natural products in anticancer therapeutics - Chaudhry, Gul-e-Saba; Zeenia, .; Akim, Abdah Md; Sung, .; Muhammad, Tengku (Japan Bilingual Publishing Co, 2024)
Cancer remains a formidable global health challenge, necessitating sustained research efforts to develop innovative and efficacious therapeutic modalities. The exploration of alternative cancer therapies has gained prominence, given the adverse side effects associated with conventional treatments like chemotherapy. Natural medicines, particularly those derived from botanical sources, emerge as a potentially more viable option for cancer treatment within the confines of therapeutic and safe dosage parameters. This comprehensive review elucidates the effective mechanisms and safety profiles related to the dosage of these natural compounds. The literature under consideration spans and has been meticulously curated from reputable databases, including PubMed, Scopus, and Google Scholar. Noteworthy natural substances encompassed in this scrutiny include gossypol, curcumin, resveratrol, genistein, anthocyanin, and hispidulin. The review outlines their respective mechanisms, therapeutic dosages, and safety perspectives within the context of cancer treatment. These compounds manifest diverse anticancer effects, ranging from the induction of apoptosis and inhibition of cell proliferation to the modulation of crucial signaling pathways. These natural compounds exhibit promising anticancer potential by targeting key facets of cancer progression, notably by i) instigating apoptosis and ii) intervening in cell cycle checkpoints. However, a more strategic and nuanced investigation is imperative to fully elucidate their optimal dosages, modes of action, and potential synergies with existing cancer treatment modalities. This critical gap in our understanding underscores the necessity for further in-depth research to optimize the therapeutic potential of these plant-derived chemicals.